Revez-cárcere: uma política dos corpos desviantes - Gerino, Alain Martins da Silva (2017)
In this paper we are working on tree moviments, divided in chapters, concerning the west mental deseases practices. First introducing the sociopolictical treatment imposed to deviant bodies, from the end os meddle age to the irruption of psychiactrical renovation; in a second moment, we approach part of the sociabilization scenario based on abre brasil virtual discuss forum and its relationship wih schizophrenia into that digital media resource, and third, last movement, highlighting the link between the deviant body and psychotropic, problematizing the used medicine effects and the implications on the current mental health politics, been essential to the analisys and perspective of patient and family in which speeches and reports were collected from the presential ABRE (Brazilian association of families, friends and the schizofrenia wrist fracture person) discussion members. Therefore, we’re referring to the literature about mental ilness, elaborated analysys from virtual group discussion, Abre_Brasil, and the ethnographical researches realized into presential Abre group as well, where familiars, caregivers and whose are classified as schizophrenic by the medical scientific agents, they all find a place where they can share and exchange their experiences on social interactions. So on, we discuss the recent methods of incarceration in the post-reform age, problematizing, as well, the psichotropic, appointed the main responsible for the estabilization and destabilization in schizophrenia. And last we close the reflection through the polictical issues into these incarceral moviments, not completely closed yet